Korinna Schönhärl, European Investment in Greece in the Nineteenth Century: A Behavioral Approach to Financial History, Routledge, Λονδίνο 2021 - ΔΕΣΥΛΛΑΣ, ΧΡΗΣΤΟΣ (Μνήμων, 2024)
Δεν διατίθεται περίληψη στα ελληνικά.